Safe and Effective Treatment for Anemic Patients With Chronic Kidney Disease: An Updated Systematic Review and Meta-Analysis on Roxadustat - Tang, Mei; Zhu, Changyu; Yan, Ting; Zhou, Yanglin; Lv, Qin; Chuan, Junlan (Frontiers in Pharmacology, 2021)
Background: Roxadustat is a new oral drug for anemia in chronic kidney disease (CKD). This study aimed to synthesize the evidence from randomized controlled trial (RCT)-based studies that estimated the efficacy and safety of roxadustat in anemia patients with non-dialysis-dependent (NDD) and dialysis-dependent (DD) CKD. Methods: We searched the PubMed, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) databases for related published studies. Moreover, we manually searched relevant pharmaceutical company websites and two international clinical trial registers to search for published and unpublished RCTs comparing roxadustat with erythropoietin-stimulating agents (ESAs) or placebo. Results: Fifteen RCTs (seven for DD-CKD patients, eight for NDD-CKD patients) were included in the meta-analyses, with 10,189 patients, 4,810 DD-CKD patients, and 5,379 NDD-CKD patients enrolled. Compared with ESAs (epoetin alfa or darbepoetin alfa) and placebo, roxadustat raised the hemoglobin level (weighted mean difference [WMD]: 0.82 g/dL; 95% confidence interval [CI]: 0.43-1.21), transferrin level (WMD: 0.5 g/L; 95% CI: 0.34-0.65), and TIBC level (WMD: 41.79 μg/dL; 95% CI: 38.67-44.92) and lowered the hepcidin level (WMD: -37.38 ng/mL; 95% CI: -46.63 to -28.12) in both the DD-CKD and NDD-CKD patients with renal anemia. Roxadustat improved hemoglobin response and lowered the ferritin and TAST levels in the NDD-CKD patients but not in the DD-CKD patients. Furthermore, there was no difference between the treatment-emergent adverse events (TEAEs) of roxadustat and that of ESAs or placebo. But the incidence of serious TEAEs in the roxadustat group was significantly higher with NDD-CKD patients (OR: 1.15; 95% CI: 1.02 to 1.29). Conclusion: This study confirmed that roxadustat therapy could alleviate the anemia of DD-CKD and NDD-CKD patients by raising the hemoglobin level and regulating iron metabolism, but increased serious incidences of treatment-emergent adverse events (TEAEs) in NDD-CKD patients.